(untitled) (Asian Journal of Social Science Studies, 2022)
Since the second industrial revolution, technological innovation has promoted manufacturing and commodity circulation, as well as social development, leading traditional society into modern development. The social relationship and structure of traditional society are in the high-speed circulation of commodities and currency. Disintegration, the development of industry reframes and stereotypes modern society. However, with the rapid economic development, the relationship between production and consumption in today’s society is distorted. Consumerism prevails, and the relationship between production and consumption cannot be balanced, which has become the biggest obstacle to establishing a correct consumption concept in my country. On the basis of expounding Marx’s concept of consumption, the article analyzes the causes of consumerism and the ways to resist the concept of overdraft consumption in today’s society, in order to promote the optimization of industrial structure and consumption structure.